Shifts in ecological strategy spectra of typical forest vegetation types across four climatic zones - Xin Han (Nature Portfolio, 2021)
Abstract Ecological strategy spectrum is the relative proportion of species in different categories of ecological strategies in a biotic community. Here, we explored ecological strategy spectra in typical forest vegetation types across four climatic zones in China. We classified ecological strategy categories by using the “StrateFy” ordination method based on three leaf functional traits. Results showed that the predominant ecological strategies of species in the tropical rainforest were CS-selected, and the predominant categories in the evergreen-deciduous broadleaved mixed forest and warm-temperate coniferous-broadleaved mixed forest were CSR and S/CSR categories respectively, whereas those in the cold-temperate coniferous forest were the S-selected ones. Ecological strategy richness of forest vegetation decreased significantly with the increase of latitude. The categories of ecological strategies with more component S increased while those with more component C decreased with the change of typical forest vegetation types from tropical rainforest through evergreen-deciduous broadleaved mixed forest and warm-temperate coniferous-broadleaved mixed forest to cool-temperate coniferous forest. Our findings highlight the usefulness of Grime’s C-S-R scheme for predicting the responses of vegetation to environmental changes, and the results are helpful in further elucidating species coexistence and community assembly in varied climatic and geographic settings.